Enhancing Creative Thinking and Artistic Competencies in Middle School Students through Visual Arts Education - Vosiyeva Aziza To‘xtaqulovna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores strategies for enhancing creative thinking and artistic competencies in 5th–7th grade students through visual arts education. It emphasizes the importance of interactive methods, project-based learning, collaborative activities, and the integration of technology in fostering creativity. The study demonstrates that modern pedagogical approaches, combined with experiential learning and individualized support, significantly improve students’ artistic skills, aesthetic perception, and creative problem-solving abilities.